Mahasiswa Ekonomi Syariah di Mata Pengguna Lulusan - Ahmad Rosyid (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
This study aims to look at the assessment PPL partner on 1 ) the performance of students Prodi EKOS 2) PPL partner satisfaction and 3 ) follow-up committee on the complaint PPL partner. Data were collected using a questionnaire and the results show that the performance PPL student Prodi EKOS are rated in the range enough categories , good and very good with the largest percentage in good categories . But for the performance mastery of foreign languages appeared less votes despite not many. As for the assessment of the committee in response to a complaint, PPL partner generally considered aswell .